Liquid chromatographic assay for metronidazole and tinidazole: pharmacokinetic and metabolic studies in human subjects. - Nilsson-Ehle, I (1981)
We developed methods for measuring metronidazole, its two major metabolites, and tinidazole in serum and urine. After treatment of each sample with an equal volume of 5% perchloric acid, the drugs were separated by reverse-phase high-pressure liquid chromatography (retention times, 6 to 18 min). Quantitation was based on spectrometry at 320 nm. These assays were sensitive, rapid, and specific, and recoveries from biological samples were quantitative. Metronidazole and tinidazole were given as rapid intravenous infusions to four healthy human volunteers. The biological half-lives of these two compounds were 5.4 and 11.1 h, respectively. The hydroxy metabolite of metronidazole appeared quickly in serum and was eliminated at a slow rate. The acetic acid metabolite of metronidazole was detected in serum at very low levels and only for a limited time. No metabolic products of tinidazole were found in serum samples. In urine, 43.7% of the administered dose of metronidazole was recovered over a period of 24 h (24.1% of the dose as the hydroxy metabolite, 12.0% as the acetic acid metabolite, and 7.6% as unchanged drug). Only 18.4% of the infused dose of tinidazole was eliminated in urine over a period of 72 h, and no metabolic products were detected.